A solvent-engineered molecule fusion strategy for rational synthesis of carbon quantum dots with multicolor bandgap fluorescence. (April 2018) - Zhan, Jing; Geng, Bijiang; Wu, Kuan; Xu, Gang; Wang, Liang; Guo, Ruiyun; Lei, Bo; Zheng, Fengfeng; Pan, Dengyu; Wu, Minghong
Abstract: We report a rational strategy for scalable production of highly fluorescent CQDs in high yields (50–92%) based on controlled molecule fusion of activated polycyclic aromatic hydrocarbon in environmentally friendly polar solvents. By simply varying the composition of reaction solvents, their bandgaps were systematically manipulated, enabling the adjustment of fluorescent emissions from blue to red. Similar to conventional organic-soluble quantum dots but distinct from extensively reported water-soluble CQDs, the CQDs engineered in polar solvents are highly soluble in organic solvents and possess main features of intrinsic bandgap transitions, including overlapping of absorption and excitation spectra, excitation-independence fluorescence, the inversely proportional relationship of the bandgaps with fluorescence peak wavelength, and mono-exponential fluorescence decay. What's more, the red-fluorescent CQDs were encapsulated by liposomes, providing good biocompatibility and excellent in vitro and in vivo imaging capabilities. Graphical abstract: Image 1